The Legal Role of State Administration in Dealing with Conflicts of Interest of Public Officials - Abdul Hamid (Dinasti Research, 2026)
Administrative law has a crucial role in regulating governance, including in the context of the roles and responsibilities of public officials. Analysis of legal views on the role of public officials is important to understand the legal basis that governs their behavior and decisions in carrying out public service duties. This study uses a normative legal approach by collecting data from various administrative law sources, including laws, regulations, and related court decisions. A critical analysis examines the legal view of public officials' roles and their implications for administrative practice. In-depth literature reviews were conducted to develop a conceptual framework grounded in relevant theories of administrative law